2013
DOI: 10.1103/physreva.88.033607
|View full text |Cite
|
Sign up to set email alerts
|

Few interacting fermions in a one-dimensional harmonic trap

Abstract: We study spin-1/2 fermions, interacting via a two-body contact potential, in a one-dimensional harmonic trap. Applying exact diagonalization, we investigate their behavior at finite interaction strength, and discuss the role of the ground-state degeneracy which occurs for sufficiently strong repulsive interaction. Even low temperature or a completely depolarizing channel may then dramatically influence the system's behavior. We calculate level occupation numbers as signatures of thermalization, and we discuss … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
128
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 87 publications
(135 citation statements)
references
References 24 publications
5
128
2
Order By: Relevance
“…Recently, the method has been successfully used for equal mass fermions confined in a harmonic trap [13,62,63] as well as for fermions of different masses [42]. First we decompose the field operatorsΨ σ (x) into the basis of the eigenfunctions of the corresponding single-particle Hamiltonians…”
Section: Exact Diagonalization Approachmentioning
confidence: 99%
“…Recently, the method has been successfully used for equal mass fermions confined in a harmonic trap [13,62,63] as well as for fermions of different masses [42]. First we decompose the field operatorsΨ σ (x) into the basis of the eigenfunctions of the corresponding single-particle Hamiltonians…”
Section: Exact Diagonalization Approachmentioning
confidence: 99%
“…In the pioneering works in this topic, the energy spectra of two trapped atoms was obtained analytically [7,8]. This research was recently followed by the study of the energy spectra of three atoms in a trap in three and reduced dimensions [9][10][11][12][13][14]. Systems of few atoms permit us to study microscopically many interesting phenomena, like the Bardeen-Cooper-Schrieffer to Bose-Einstein-condensate (BCS-BEC) crossover [15].…”
Section: Introductionmentioning
confidence: 99%
“…(21). In order to obtain the same energy functional as (23), the only way is to consider the following effective Hamiltonian…”
Section: Spin-1/2 Fermionsmentioning
confidence: 99%
“…Recently, taking advantage of the high controllability of a few particles in the trapped ultra-cold systems [20], a number of studies have revealed the energy spectra and correlation effects for a few spin-1/2 fermions by numerical simulations [21][22][23][24]. In the strong coupling regime, an effective Heisenberg spin-chain model has also been deduced [25][26][27][28].…”
mentioning
confidence: 99%